2023
DOI: 10.1007/s00894-023-05528-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal morphology prediction of CL-20 and 1,4-DNI co-crystal at different temperatures

Abstract: Using the attachment energy (AE) model and molecular dynamics (MD) methods, the morphologies of hexanitrohexaazaisowurtzitane (CL-20) and 1,4-dinitroimidazole (1,4-DNI) co-crystal under vacuum or solvent at different temperatures were predicted. The CL-20/1,4-DNI co-crystal has six important growth crystal planes: (002), ( 011), ( 101), (11-1), (110), ( 111). The area of ( 002), ( 101), and (011) planes account for a relatively large proportion, which are important crystal planes that affect the crystal morpho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results showed that the theoretical predictions are in good agreement with the experiment. The simulation results can provide guidance for the crystallization of CL-20/1,4-DNI to obtain a nearly spherical crystal morphology [120].…”
Section: Cocrystals Of Cl-20 With 14-dnimentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed that the theoretical predictions are in good agreement with the experiment. The simulation results can provide guidance for the crystallization of CL-20/1,4-DNI to obtain a nearly spherical crystal morphology [120].…”
Section: Cocrystals Of Cl-20 With 14-dnimentioning
confidence: 98%
“…In the work of Li et al, the CL-20/1,4-DNI unit cell structure was geometrically optimized by the COMPASS force field [120]. The AE model was used to predict the morphology of CL-20/1,4-DNI under vacuum, resulting in the most morphologically important growth planes.…”
Section: Cocrystals Of Cl-20 With 14-dnimentioning
confidence: 99%